Alterations in the gut microbiota composition in the obesity phenotype of heart failure with preserved ejection fraction. (3rd October 2022) - Rokach, Y; Abedat, S; Nachman, D; Dana, S; Qadan, A; Beeri, R; Amir, O; Asleh, R
Abstract: Introduction: Obesity is one of the most common phenotypes of heart failure with preserved ejection fraction (HFpEF). A growing body of evidence indicates that obesity is characterized by compositional alterations in the intestinal microbiota and its metabolites, collectively referred as dysbiosis. Purpose: We sought to investigate whether the obese phenotype of HFpEF is mediated by further alterations in the microbiota and whether gut dysbiosis fuels metabolic inflammation leading to progression of HFpEF. Methods: HFpEF was induced in C57/black mice by high-fat diet and inhibition of NO synthesis (a "2-hit-model") (Figure 1A). High-frequency echocardiography was performed to assess diastolic function. Blood pressure (BP) was measured using CODA non-invasive tail-cuff system. For human studies, patients with obese HFpEF as well as obese and non-obese healthy individuals were prospectively recruited. Gut microbial DNA was subjected to 16S ribosomal RNA gene sequencing, and the differences in abundance and composition of bacteria were defined both in humans and mice. Results: In mice, the 2-hit model demonstrated significantly increased BP and impaired diastolic function in the obese HFpEF group (Figure 1B). Microbiome analysis showed significant differences in the gut microbial diversity and composition in the obese HFpEF compared to the non-HFpEF obese and chow-fed mice (Figure 1C). Similarly, human microbiome sequencing showed significant gut bacterial alterations in the diversity and composition of bacteria with more profound dysbiosis observed in the obese HFpEF patients compared to the obese and lean healthy individuals (Figure 1D). Conclusions: We provide evidence in humans as well as in a murine animal model that the obese HFpEF phenotype is associated with more pronounced gut dysbiosis compared to the non-HFpEF obesity state. Further research will elucidate the causative link between gut dysbiosis and HFpEF manifestation and the mechanistic insights into the implication of gut microbiota in HFpEF progression. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Israel science foundation